PENGARUH VARIABEL KEUANGAN TERHADAP HARGA SAHAM PADA INDEX LQ45 DI BURSA EFEK INDONESIA - Debi Septiani (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2022)
The aim of this study is to investigate the influence of financial variable on stock price of Index LQ45 in Indonesia Stock Exchange, such as Return on Equity (ROE), Earning Per Share (EPS), Current Ratio (CR), Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR). The data was obtained from the financial statement of Indonesia Capital Market Directory (ICMD) based on the publication of the Indonesia Stock Exchange between 2012 and 2018. The data were analyzed by using multiple linear regression analysis. The result indicated that there was significant effect simultaneously between financial variable [Return on Equity (ROE), Earning Per Share (EPS), Current Ratio (CR), Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR)], while partially shows that the five independent variables which indicated the presence of significant influence were Return on Equity (ROE), Earning Per Share (EPS) on stock price of Index LQ45 in Indonesia Stock Exchange. This study provided evidence about the financial variable on stock price of Index LQ45 shows that Return On Equity (ROE) Ratio was more dominant on Index LQ45.